2013
DOI: 10.1128/cmr.00077-12
|View full text |Cite
|
Sign up to set email alerts
|

Human Rhinoviruses

Abstract: SUMMARYHuman rhinoviruses (HRVs), first discovered in the 1950s, are responsible for more than one-half of cold-like illnesses and cost billions of dollars annually in medical visits and missed days of work. Advances in molecular methods have enhanced our understanding of the genomic structure of HRV and have led to the characterization of three genetically distinct HRV groups, designated groups A, B, and C, within the genusEnterovirusand the familyPicornaviridae. HRVs are traditionally associated with upper r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
680
2
37

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 608 publications
(739 citation statements)
references
References 284 publications
(330 reference statements)
20
680
2
37
Order By: Relevance
“…The clinical spectrum of rhinovirus infection can range from asymptomatic to more severe lower respiratory tract illness such as obliterative bronchiolitis and pneumonia [1]. Rhinovirus is recognised as a major trigger of asthma and chronic obstructive pulmonary disease (COPD) exacerbations [2].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical spectrum of rhinovirus infection can range from asymptomatic to more severe lower respiratory tract illness such as obliterative bronchiolitis and pneumonia [1]. Rhinovirus is recognised as a major trigger of asthma and chronic obstructive pulmonary disease (COPD) exacerbations [2].…”
Section: Introductionmentioning
confidence: 99%
“…4 -8 With the use of sensitive polymerase chain reaction (PCR) and other molecular assays for diagnosis and typing, the detection rates of rhinoviruses have increased, group A, B, and C rhinoviruses have been identified, and the spectrum of rhinovirus illnesses has been better recognized. 9 However, the illness burden of rhinovirus infections in young children is poorly defined. Previous studies have been either small, conducted in selected populations, done before the era of PCR diagnostics, or they have not covered noncomplicated upper respiratory tract infections that may contribute substantially to the disease burden because of high frequency.…”
mentioning
confidence: 99%
“…Rhinoviruses are the most common cause of upper respiratory tract infections (URIs). 1 Recent studies have shown an increasing prevalence of asymptomatic rhinovirus infections. [2][3][4] Picornavirus nucleic acids are typically shed from the upper respiratory tract for 1 to 3 weeks after infection.…”
mentioning
confidence: 99%